COAL DRYING PROCESS IN A FLUIDIZED BED UNIT - M. Kurbanbaeva; R. Seitimbetov; M. Bekimbetov (Western European Studies, 2025)
The article presents the process of preparing coal for grinding at conventional thermal power plants, analyzing its shortcomings and ways to address them. As a result of the analysis, the results of experiments conducted to study the coal drying process in a fluidized bed apparatus were presented, and drying curves and drying rate were constructed. The dependence of the obtained results not only on the grade of the coal but also on its fineness is shown in specific examples. The results are compared with the results obtained using existing methods, and the sequence of experiments is fully described. In addition, there are studies related to the study of changes in the moisture content of coal and air.
Keywords: Boiling layer dryer; humidity; ash content